Inhibitors of thiol-mediated uptake. Issue 2 (18th November 2020) - Cheng, Yangyang; Pham, Anh-Tuan; Kato, Takehiro; Lim, Bumhee; Moreau, Dimitri; López-Andarias, Javier; Zong, Lili; Sakai, Naomi; Matile, Stefan
Abstract : Thiol-reactive inhibitors for the cellular entry of cyclic oligochalcogenide (COC) transporters and SARS-CoV-2 spike pseudo-lentivirus are reported. Abstract : Ellman's reagent has caused substantial confusion and concern as a probe for thiol-mediated uptake because it is the only established inhibitor available but works neither efficiently nor reliably. Here we use fluorescent cyclic oligochalcogenides that enter cells by thiol-mediated uptake to systematically screen for more potent inhibitors, including epidithiodiketopiperazines, benzopolysulfanes, disulfide-bridged γ-turned peptides, heteroaromatic sulfones and cyclic thiosulfonates, thiosulfinates and disulfides. With nanomolar activity, the best inhibitors identified are more than 5000 times better than Ellman's reagent. Different activities found with different reporters reveal thiol-mediated uptake as a complex multitarget process. Preliminary results on the inhibition of the cellular uptake of pseudo-lentivectors expressing SARS-CoV-2 spike protein do not exclude potential of efficient inhibitors of thiol-mediated uptake for the development of new antivirals.